PERUBAHAN RELASI KUASA ULAMA DAN SULTAN DI KERAJAAN MATARAM ISLAM 1613-1677 : Indonesia - Muhammad Ilham Aziz; Isna Zakiya Nurul Muftaza (JUSAN: Jurnal Sejarah Peradaban Islam Indonesia, 2025)
Abstract: This article discusses changes in the power relations of the ulama and the Sultan in the Islamic Mataram Kingdom. In the early days of the establishment of Mataram Islam, the Ulama had an important political role, namely as religious and political advisers in the kingdom. As time went on, there was a change in power relations between the ulama and the sultan, the ulama no longer had a higher position than the king. Some of the ulema became royal officials and worked under the sultan's authority. Even the honorary titles that were originally only used by the ulema were finally used by the sultans to show the king's power as a political leader as well as a religious leader. The main issues that will be discussed in this study include socio-political conditions in the Islamic Mataram Kingdom, the position and relations of the ulama and the sultan and finally discusses changes in the power relations between the ulama and the sultan. This study was developed using the political history method. The findings of this study are that changes in the relationship between the ulama and the sultan occurred due to efforts to legitimize power by the sultan, the characteristics of the rulers and the VOC's interference in the government in Mataram. Keywords: Power relations, Ulama, Sultan, Mataram Islam Kingdom.